RUSSIAN PRIVATE MILITARY COMPANIES AS A CATALYST FOR STRATEGIC AMBIGUITY AND DECEPTION - Śledź, Piotr (Torun International Studies, 2025)
Russian private military companies (PMCs) – being in fact neither private nor companies – have become an important instrument of strategic influence for the Kremlin. Apart from their military activity, as manifested especially during the war in Ukraine, such deployments abroad induce strategic ambiguity and deception in line with the national foreign and security policy objectives. The examination of this influence is the main research problem of the study. For this purpose a seven-element analytical model by Robert Mandel concerning strategic manipulation has been employed. This allows to emphasize these elements of the Russian PMCs’ specificity that enable actions of this kind, present Russia’s strategic objectives being pursued this way and assess the efficiency of the discussed approach. The approach applied in the paper, unlike most of the publications concerning those entities, allows to address the use of PMCs by Russia not as military power providers but as actors making a psychological impact on others both directly (by performing information and psychological operations) and indirectly (by shaping the perception of the Russian Federation internationally). As the paper presents, the latter might be considered crucial, as Russia benefits from having a handy tool for, among others, increasing the threat perception in targeted countries or regions by putting political-military pressure “below the threshold of war” and providing itself with low-cost power projection capabilities (even if very often unreliable).